Great Moments in the History of Life - Shaw, George H. (Popular Science,, 2018)
A non-technical (but serious) treatment of those parts of Earth history leading up to human history, as well as some pre-historical aspects of humanity. Many "events" in Earth's history necessarily preceded the emergence of human beings (and intelligence). Geology has provided us with a great deal of information about these various steps on the way to intelligent life, and how and why they were important. Some of these events were on a cosmic scale (no universe - no life!), some were planetological/astronomical (no Earth - no life), some were essentially chemical (how did life emerge in the primordial ocean and why do we have oxygen in the atmosphere?), and some were details of evolutionary history (how did life colonize the land and how did mammals develop?). In this book an enthusiastic professor of geosciences presents a broad introduction from the Big Bang to the present and into the future, lucidly explaining aspects from various disciplines to interested, non-specialist readers.